Implementation of the triple bottom line concept to improve sustainable marketing performance - Purnama, Yunus Indra (Journal of Economics and Business Letters, 2024)
This study intends to observe the implementation of triple botton line in improving sustainable marketing performance. Sustainable marketing is a concept that combines socially and environmentally responsible marketing practices to achieve long-term sustainable goals. With a Triple Bottom Line (TBL)-based approach, it is a business concept that measures company performance not only based on finances, but also takes into account the social and environmental impacts of its business activities. TBL describes three main dimensions that companies must consider, namely economic or financial, social responsibility, and environmental sustainability. The three dimensions are interrelated and must be integrated to achieve optimal balance. In the context of sustainable marketing performance, the Triple Bottom Line provides a foundation for analyzing the impact of a company's marketing activities thoroughly. The application of Triple Bottom Line in sustainable marketing performance not only looks at financial gain, but also considers good relationships with customers, positive contributions to society, and efforts to maintain environmental sustainability. This creates long-term value for the company and reflects a commitment to the overall development of the company. Sustainable marketing can contribute to a company's sustainability not only through everyday practices that minimize environmental impact, but also by implementing new policies and strategies to support the broader concept of corporate sustainability as a fundamental part of the entity's economy. Research on the implementation of triple botton line and sustainable marketing performance is carried out with a qualitative approach using literature review methods including research results then analyzing them carefully and in depth in order to get results that are in accordance with the expected goals